Changes to national postgraduate medical education during COVID-19: a scoping review of practice and impact within the UK - Gillian Vance; Bryan Burford; Megan E L Brown; Gabrielle Finn (BMJ Open)
Objectives Explore what is known about the impact of changes made at a national level to UK postgraduate medical education during COVID-19.Design A scoping review, following Arksey and O’Malley’s framework, reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews Checklist.Data sources Ovid MEDLINE, Ovid Embase and ERIC were searched for peer-reviewed literature, and grey literature was searched via DuckDuckGo. The initial search was conducted on 17 January 2023 and updated on 5 June 2024. Forward citation tracking was performed.Eligibility criteria English-language studies of any design examining national-level adaptations to postgraduate medical education (eg, curricula, examinations and Annual Review of Competency Panels (ARCPs)) within the UK during the COVID-19 pandemic. Studies were excluded, which focused solely on undergraduate education, international settings, grassroots-level changes (eg, to individual teaching sessions), or where full text was unobtainable.Data extraction and synthesis Data were extracted using a piloted charting form and analysed thematically to identify recurring patterns across studies. Basic numerical data were collected to describe study characteristics.Results Of 1067 records screened, 30 studies met inclusion criteria. Most were cross-sectional surveys, with a strong representation from surgical and craft specialties. Four themes were identified: (1) impact on career development (including concerns about career delays and shifts in aspirations); (2) impact on trainee progression (highlighting delays due to ARCP outcomes 10.1/10.2 and reduced procedure accreditation); (3) changes in teaching and learning (such as a shift to online learning and cancelled rotations) and (4) supervision and support (revealing mixed experiences, with reports of burnout and inadequate organisational guidance). The systemic impact was uneven across specialties and training stages.Conclusions National-level changes mitigated immediate educational disruptions but are beginning to reveal long-term consequences for career development, workforce planning and trainee well-being, highlighting the need for resilient and equitable future frameworks.